Chromoanagenesis Event Underlies a de novo Pericentric and Multiple Paracentric Inversions in a Single Chromosome Causing Coffin–Siris Syndrome - Grochowski, Christopher M.; Krepischi, Ana C. V.; Eisfeldt, Jesper; Du, Haowei; Bertola, Debora R.; Oliveira, Danyllo; Costa, Silvia S.; Lupski, James R.; Lindstrand, Anna; Carvalho, Claudia M. B. (Frontiers in Genetics, 2021)
Chromoanagenesis is a descriptive term that encompasses classes of catastrophic mutagenic processes that generate localized and complex chromosome rearrangements in both somatic and germline genomes. Herein we describe a 5-year-old female presenting with a constellation of clinical features consistent with a clinical diagnosis of Coffin-Siris syndrome 1 (CSS1). Initial G-banded karyotyping detected a 90 Mb pericentric and 47 Mb paracentric inversion on a single chromosome. Subsequent analysis using short-read whole genome sequencing, and genomic optical mapping revealed additional inversions, all clustered on chromosome 6, one of them disrupting ARID1B for which haploinsufficiency leading to CSS1. In all, the resolved derivative chromosome architecture presents four de novo inversions, one pericentric and three paracentric, involving six breakpoint junctions in what appears to be a shuffling of genomic material on this chromosome. Each junction was resolved to nucleotide-level resolution with mutational signatures suggestive of non-homologous end joining. The disruption of the gene ARID1B is shown to occur between the 4th and 5th exon of the canonical transcript with subsequent qPCR studies confirming a decrease in ARID1B expression in the patient versus healthy controls. Deciphering the underlying genomic architecture of chromosomal rearrangements and complex structural variants may require multiple technologies and can be critical to elucidating the molecular etiology of a patient’s clinical phenotype or resolving unsolved Mendelian disease cases.